The Combined Effect of Cold and Moisture on Manual Performance. (February 2018) - Ray, Matthew; Sanli, Elizabeth; Brown, Robert; Ennis, Kerri Ann; Carnahan, Heather
Objective: The aim of this study was to investigate the combined effect of cold and moisture on manual performance and tactile sensitivity. Background: People working in the ocean environment often perform manual work in cold and wet conditions. Although the independent effects of cold and moisture on hand function are known, their combined effect has not been investigated. Method: Participants completed sensory (Touch-Test, two-point discrimination) and motor (Purdue Pegboard, Grooved Pegboard, reef knot untying) tests in the following conditions: dry hand, wet hand, cold hand, and cold and wet hand. Results: For the Purdue Pegboard and knot untying tasks, the greatest decrement in performance was observed in the cold-and-wet-hand condition, whereas the decrements seen in the cold-hand and wet-hand conditions were similar. In the Grooved Pegboard task, the performance decrements exhibited in the cold-and-wet-hand condition and the cold-hand condition were similar, whereas no decrement was observed in the wet-hand condition. Tactile sensitivity was reduced in the cold conditions for the Touch-Test but not the two-point discrimination test. Conclusion: The combined effect of cold and moisture led to the largest performance decrements except when intrinsic object properties helped with grasp maintenance. The independent effects of cold and moisture on manual performance were comparable. Application: Tools and equipment for use in the cold ocean environment should be designed to minimize the effects of cold and moisture on manual performance by including object properties that enhance grasp maintenance and minimize the fine-dexterity requirements.